ANALISIS KINERJA SIMPANG TAK BERSINYAL (STUDI KASUS: SIMPANG TLAJUNG GUNUNG PUTRI, KABUPATEN BOGOR) - Leimena, Intan Melenia; Wahyurianti, Syafira; Wiyono, Eko; Rizal, Rikki Sofyan (Jurnal Ilmiah Teknologi Infomasi Terapan, 2021)
The traffic jam in various locations causes a decrease in the road service level and crossroads. To control the level of a traffic jam it is required to improve the intersection performance to reduce barriers, increase capacity, and reduce accidents. The purpose of this final project is to help solve the congestion problem that occurs at the Simpang Tlajung Gunung Putri. The data used are primary data that obtained through field surveys and the secondary data obtained from the Central Bureau of Statistics of Bogor District and various journals. The data analysis method uses manual calculations in accordance with the Indonesian Highway Capacity Manual (MKJI 1997). The existing condition of Simpang Gunung Putri Tlajung after being analyzed showed poor results with a capacity of 3676,509 pcu/hour; vehicle volume of 5622,27 pcu/hour; degree of saturated (DS) of 1,53; delay (D) -22,532 sec/pcu; queue probability of 218% (upper limit) and 100% (lower limit) and had a very poor level of intersection service. In overcoming the performance problems of Simpang Tlajung Gunung Putri 9 (nine) alternative solutions were carried out. The solution to the problem used is the last alternative solution, namely a combination of the installation of prohibited stop signs, restrictions on heavy vehicle operating hours, prohibition of turning right from the South approach (Narogong Highway To Cileungsi), the East approach (Wanaherang Highway) made one way to The Cibubur Alternative Road, and the South approach (Narogong Highway To Cileungsi) are made in one way towards Gunung Putri that shows a capacity value of 5695,091 pcu/hour; degree of saturated (DS) of 0,75; delay (D) 12,297 sec/pcu queue probability of 23%-46% and had a service level in category B which means the performance of the intersection is in good condition.